Pelatihan Manajemen untuk Peningkatan Kualitas Pengelolaan Taman Pendidikan Al-Quran - Adim Firmansah; Aripriharta Aripriharta; Ahmad Munjin Nasih; Ahmad Taufiq; Nandang Mufti; Satia Nur Maharani (STAI Auliaurrasyidin Tembilahan, 2021)
Al-Quran Education Park (TPQ) is one of the places to learn that is spread in almost all parts of Indonesia. Especially for Malang and surrounding areas, the management of TPQ is still not optimal, for example TPQ in Mojosari Village, Gambiran, Kepanjen District, Malang Regency. Management that has not reached the good category needs a helping hand from the UM abdimas team, considering the UM RENSTRA which wants to realize the downstreaming of science and research results. The Abdimas team consisting of lecturers across faculties, apart from having experience in research and service, also has a real role in their respective regions regarding TPQ and takmir. The undoubted competence of the team and the additional composition of students are expected to assist the implementation of management training activities at partner TPQ. Management training is expected to improve the quality of TPQ management from several aspects, namely: finance, programs, and governance. This activity is carried out using training methods (knowledge and skills) which are carried out in a structured and periodic manner. Each activity evaluates (measures) the achievement/success of the Abdimas program. Questionnaires are provided as data collectors for final analysis. In general, activities have been running smoothly and the public is quite satisfied with the index reaching 0.75.